Empowering Hypertension Patients: How Flipcharts Improve Self-Management Skills - Febtrina, Rizka; Afrianti, Yusfika; Wardah, Wardah; Sari, Indah Indreani (Journal of Nursing Care, 2024)
Hypertension is an incurable condition; thus, it is essential to control it by improving patient self-management, particularly through education. This study seeks to assess the impact of instruction through flipcharts on self-management in individuals with hypertension. The study employs a quasi-experimental design featuring pre- and post-tests, lacking a control group. This study's population comprises hypertension patients, with a sample size of 21 respondents from the Simpang Tiga Community Health Center in Pekanbaru City, gathered between May 20 and June 3, 2024. The research instrument employed is the Hypertension Self-Management Behavior Questionnaire. This study was executed during two meetings within a fortnight. The analysis included a paired t-test. The research findings indicated that the mean self-management score prior to the intervention was 85.90, whereas the mean self-management score subsequent to the intervention rose to 114.62. The paired test findings revealed a p-value of 0.000 (<0.05). It can be stated that teaching utilizing flipcharts influences the self-management capabilities of patients with hypertension. This research aims to establish flipchart media as a tool for disseminating information and health education to the population. Further studies should explore health education interventions utilizing flipchart media for more non-communicable diseases.